2014
DOI: 10.1016/j.exger.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish (Danio rerio) as a model for the study of aging and exercise: Physical ability and trainability decrease with age

Abstract: A rapidly aging global population has motivated the development and use of models for human aging. Studies on aging have shown parallels between zebrafish and humans at the internal organization level; however, few parallels have been studied at the whole-organism level. Furthermore, the effectiveness of exercise as a method to mitigate the effects of aging has not been studied in zebrafish. We investigated the effects of aging and intermittent exercise on swimming performance, kinematics and behavior. Young, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 57 publications
11
120
1
Order By: Relevance
“…The population density was 3 fish per litre. The experiment lasted 13 weeks so that fish age at the end of the experiment was between 16 and 22 months (adults) corresponding to approximately 48% of the average life expectancy in the laboratory [3].…”
Section: Methodsmentioning
confidence: 99%
“…The population density was 3 fish per litre. The experiment lasted 13 weeks so that fish age at the end of the experiment was between 16 and 22 months (adults) corresponding to approximately 48% of the average life expectancy in the laboratory [3].…”
Section: Methodsmentioning
confidence: 99%
“…Our study examining critical swimming speed and evaluating exercise tolerance showed that critical swimming speed decreased significantly and exercise tolerance declined with aging in zebrafish. A recent study of zebrafish by Gilbert et al [5] has reported that not only swimming speed and endurance but also the ability of exercise training to improve performance decreased with age. The swimming challenge test in fish is similar to the treadmill test in humans in that it describes exercise capacity and endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Its short life span, transparent embryo, gradual physiological aging, and amenability to genetic engineering have caused it to be used for many development and disease studies. Like humans, aged zebrafish have reduced exercise tolerance [5], degenerative changes in the spinal column [6], and cognitive decline [7,8]. And like humans, differences in genetics have been shown to contribute to differences in life span [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, we hypothesize that these age-related patterns are common features of the relationship between age and locomotor performance in a wide range of organisms. The shape of the patterns seems to match descriptions of other age-related locomotor performances in different species, such as flight performances in Drosophila (31), honeybees (32), and codling moths (33), maximal sprint speed in dogs and horses (34)(35)(36), physical activity in different rodents and monkeys (16,27,28), grip strength in mouse lemurs (15), hunting rates and success in wolves (37), swimming speed in zebrafish (38), and voluntary activity and electrotactic behavior in C. elegans (29,39). Likewise, other performance traits might follow a similar pattern, such as biting force in mouse lemur (40), cognitive performances in Rhesus monkey (41), attentiveness in domestic dogs (42), pharynx pumping rate in C. elegans (43), and perhaps even photosynthetic yield in cotton leaves (44).…”
Section: A Robust Nonlinear Pattern Describes Age-related Physiologicmentioning
confidence: 99%